(untitled) (Bangladesh Journal of Plant Taxonomy, 2016)
The present paper deals with the phylogeny and inter-and intragenic relationships using four chloroplast DNA sequences within 19 Galium L. species from Korea and Japan. Maximum parsimony and Bayesian analyses were conducted to clarify the relationships among the section and species. The strict consensus tree had three main clades. Clade I comprises of the only individuals of G. paradoxum Maximowicz (sect. Cymogalia), which is distinguished by opposite leaves in the genus, supported by the 100% bootstrap value (PP: 0.98); Clade II consists of members of eight sections (sect. Galium, sect. Hylaea, sect. Kolgyda, sect. Trachygalium, sect. Leptogalium, sect. Orientigalium, sect. Aparine, and sect. Leiogalium); Clade III comprises members of eight sections (sect. Baccogalium, sect. Lophogalium, sect. Platygalium, sect. Relbunium, sect. Depauperata, sect. Aparinoides, sect. Leiogalium and Trachygalium). The sect. Leptogalium which includes two taxa namely G. tokyoense Makino and G. dahuricum var. lasiocarpum (Makino) Nakai is paraphyletic. Four taxa of Trachygalium group (G. trachyspermum A. Gray, G. gracilens (A. Gray) Makino, G. pogonanthum Franch. & Sav., G. koreanum Nakai) were placed from sect. Cymogalia to sect. Platygalium based on molecular and morphological data. Bangladesh J. Plant Taxon. 23(2): 237-246, 2016 (December)